The Effectiveness of STEAM-Based Multisensory Model Implementation Training For Strenghtening Teacher Competence - Khikmah Novitasari; Novianti Retno Utami; Herdi Handoko; Yulian Agus Suminar (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2022)
Teachers, as professionals in early childhood education institutions, must continually improve their competencies to keep up with the era. Learning prepared for children to face the 21st century is knowledge based on Science, Technology, Engineering, the Arts, and Mathematics which can be applied by activating all of the child's senses. One of the ways to improve competence is through training activities. This study aims to determine the effectiveness of STEAM-based multisensory model implementation training activities to increase teacher competence at IGRA (Raudhatul Athfal Teacher Association), Dukun District, Magelang Regency. The research subjects were 38 teachers. The training process's effectiveness was measured using Instrument Authentic Assessment Based on Teaching and Learning Trajectory with Student Activity Sheets (AABTL with SAS). The results showed that the STEAM-based multisensory model implementation training for strengthening teacher competence at IGRA, Dukun District was effective with an average score of 82.3% of trainees. The material most mastered by participants was multisensory material, while the material less mastered by participants was STEAM material in Early Childhood Education.